Feasibility of Telephone Follow-Up after Critical Care Discharge - Broderick, Julie; Martin-Loeches, Ignacio (My University, 2020)
Background: Critical care has evolved from a primary focus on short-term survival, with greater attention being placed on longer-term health care outcomes. It is not known how best to implement follow-up after critical care discharge. Study aims were to (1) assess the uptake and feasibility of telephone follow-up after a critical care stay and (2) profile overall physical status and recovery during the sub-acute recovery period using a telephone follow-up assessment. Methods: Adults who had been admitted to critical care units of St. James’s Hospital, Dublin, for >72 h were followed up by telephone 3–9 months post discharge from critical care. The telephone assessment consisted of a battery of questionnaires (including the SF-36 questionnaire and the Clinical Frailty Scale) and examined quality of life, frailty, employment status, and feasibility of telephone follow-up. Results: Sixty five percent (n = 91) of eligible participants were reachable by telephone. Of these, 80% (n = 73) participated in data collection. Only 7% (n = 5) expressed a preference for face-to-face hospital-based follow-up as opposed to telephone follow-up. For the SF-36, scores were lower in a number of physical health domains as compared to population norms. Frailty increased in 43.2% (n = 32) of participants compared to pre-admission status. Two-thirds (n = 48) reported being >70% physically recovered. Conclusion: Results showed that telephone follow-up is a useful contact method for a typically hard-to-reach population. Deficits in physical health and frailty were noted in the sub-acute period after discharge from critical care.
PUBLISHED
Keywords: Frailty; Quality of life; Recovery; Intensive care; Critical care; Telephone; Ageing; PHYSIOTHERAPY; Respiratory Medicine; Age-related disability; Chronic Health Condition; Mobility impairment; Physical disability; Health